Violating the Maxims of Quality and Quantity on the ‘Demo Sabun’ Sketch of Extravaganza Situation Comedy TV - Setia Rini (IAIN Salatiga, 2010)
This study focuses on analyzing the violation of maxims as proposed by Grice in his cooperative principles. The subject of the study is on one of TV sitcoms broadcasted by one of the private owned TV station in Indonesia. The writer collected the data by transcribing the dialogues among the comedian in one sketch. In this modern era there are many busy people who need such kind of entertainment to lead them release their fatigue after having a day work. This situation invites some creative people to produce humor which is then packaged in the form situation comedy. These sitcoms can be broadcasted in many television stations now. In creating such funny expressions, there must be the violation on some maxims. By violating the maxims; the humorous verbal interaction can be achieved. The writer found that there are two types of violation on maxims of quality and quantity in one of the extravaganza’s sketches.keywords; Violation; Maxims, Humor